1996
DOI: 10.1017/s0954579400007161
|View full text |Cite
|
Sign up to set email alerts
|

Childhood-onset versus adolescent-onset antisocial conduct problems in males: Natural history from ages 3 to 18 years

Abstract: We report data that support the distinction between childhood-onset and adolescent-onset type conduct problems. Natural histories are described from a representative birth cohort of 457 males studied longitudinally from age 3 to 18 years. Childhood-and adolescent-onset cases differed on temperament as early as age 3 years, but almost half of childhood-onset cases did not become seriously delinquent. Type comparisons were consistent with our contention that males whose antisocial behavior follows a life-course-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
710
8
35

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 815 publications
(797 citation statements)
references
References 46 publications
44
710
8
35
Order By: Relevance
“…Our finding that the EOP trajectory had the highest risk of poor early adult outcomes is consistent with previous reports. It has been posited [19] that EOP individuals differ from AO individuals in terms of negative predisposing genetic factors and early neurocognitive characteristics. More recent studies have also shown that these individuals present with increased levels of environmental risk factors in prenatal stages [13] and early age [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that the EOP trajectory had the highest risk of poor early adult outcomes is consistent with previous reports. It has been posited [19] that EOP individuals differ from AO individuals in terms of negative predisposing genetic factors and early neurocognitive characteristics. More recent studies have also shown that these individuals present with increased levels of environmental risk factors in prenatal stages [13] and early age [36].…”
Section: Discussionmentioning
confidence: 99%
“…Early risk factors also account for AO individuals, particularly parental instability [16], low IQ and under controlled temperament [17]. Concomitant risk factors in adolescents with conduct problems include high-risk sexual behaviour, high levels of academic difficulties, and substance use [18,19]. Regarding CL individuals, previous research showed that risk factors are similar to those seen in EOP such as maltreatment, family conflict, and maternal maladjustment [4,20] but present with lower levels compared to EOP.…”
Section: Introductionmentioning
confidence: 99%
“…Life-course-persistent antisocial behavior is also associated with a different set of childhood variables (Moffitt, 1990;Moffitt et al 1996;Moffitt & Caspi, 2001), and antisocial behavior co-morbid with ADHD shows a different profile of family risk factors (Lahey et al 1988;Moffitt, 1990;Barkley et al 1991;Hinshaw, 1994;Faraone et al 1995) and a more severe prognosis (Moffitt, 1990). The co-morbid type that begins earlier may also be more strongly genetically influenced (Silberg et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst other youth, however, the onset of antisocial behavior occurs in adolescence and is believed to be relatively more common, limited to adolescence and early adulthood, and with less gender disparity when compared to early onset pathway (Moffitt 1993). Moffitt and colleagues Moffitt et al 1996Moffitt et al , 2002 used longitudinal data and identified youth following the childhood or the adolescent onset path of ASB. In accordance with the theory, these researchers showed that although 5-10% of children first engage in ASB in childhood, a considerably larger percentage starts in adolescence (26%).…”
mentioning
confidence: 99%
“…Specifically, studies that supported the childhood vs. adolescent onset distinction often lumped different forms of ASB into a single score. Although the specific items differed across studies, the ASB scores in each study were comprised of various behaviors including oppositional behavior, physical aggression, vandalism, and property offenses (Fergusson and Horwood 2002;Moffitt et al 1996Moffitt et al , 2002van Lier et al 2007). These different behaviors, however, may have specific developmental courses Tremblay 2003).…”
mentioning
confidence: 99%